Analysis Of Factors Influencing The Incident Of Urinary Tract Infections In Pregnancy - Andi Alya Nabilah; Anna Sari Dewi; Hasliyawati Hasan; Masita Fujiko M.Said; Muhammadong, Muhammadong (Sean Institute, 2024)
Urinary tract infections are one of the most common health problems. There are several factors that influence the occurrence of urinary tract infections during pregnancy, namely, age, education, employment, income, gestational age also influence the occurrence of UTI. To analyze the factors that influence the incidence of urinary tract infections in pregnancy. This type of research uses Literature Review. A literature review study is a method used to collect data or sources related to a particular topic which can be obtained from various sources such as journals, books, the internet and other libraries. The design of this research is a Narrative Review design by analyzing 20 journals. Got it20 journals were reviewed, regarding the influence of the incidence of urinary tract infections on pregnancy where education, employment, level of knowledge, sexual relations, genital hygiene, socio-economics had a significant influence. There is a significant relationship between education, employment, level of knowledge, sexual relations, genital hygiene, socio-economics and the incidence of UTIs in pregnancy.